East Indian Woman, Trinidad, B.W.I. - (:unkn) unknown (Queen's Park Hotel Co. Ltd., Trinidad [Printed in England], 2008)
A portrait of a woman of East Indian origin wearing traditional Hindu garments: sari, choli and a skirt. She is adorned with a nose ring, bangles on her wrists, armlets on both arms, a mang tikka in her hair, earrings and necklaces. Postcard No. 10.
Colour: Brown and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; East Indians--Trinidad and Tobago; Huts--Trinidad and Tobago; Ethnic costume--India; Hair ornaments--India; Nose rings--India; Earrings--India; Bracelets--India; Jewelry--India